Ownership Structure of Cooperatives as an Environmental Buffer* - Núñez‐Nickel, Manuel; Moyano‐Fuentes, José (Journal of Management Studies, 2004)
ABSTRACT In this paper, we propose that the ownership structure in the cooperative form acts as an environmental buffer. It is a mechanism to obtain stronger linkages with suppliers by internalizing them, and in this way, obtaining fundamental resources. Using this strategy, the cooperative form can isolate itself from adverse environments and from competition from other organizational forms. Although cooperatives have higher survival probability in any economic context, in rival ideological environments they have less support than other organizational forms. To test these ideas, we have chosen data from the Spanish olive oil milling industry for 1944–98. During this period, Spain changed from a dictatorial to a democratic regime and from a self‐subsistence economy in the post civil‐war period to a broad liberal international economy. The results show that, whereas other organizational forms are affected by economic and ideological influences, the cooperative form isolates itself by changing the competition level.